Quantum physics dropwise. Issue 3 (March 2018) - Bohr, Tomas
Classical wave-driven particles can mimic basic quantum properties, but how far this parallel extends is yet to be seen. Evidence for quantum-like mirages in a system of droplets moving on a fluid surface pushes the analogy into many-body territory.